2013
DOI: 10.1111/1471-0528.12221
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of induction of labour at term with aFoley catheter compared to vaginal prostaglandin E2gel (PROBAATtrial)

Abstract: Objective To assess the economic consequences of labour induction with Foley catheter compared to prostaglandin E 2 gel.Design Economic evaluation alongside a randomised controlled trial.Setting Obstetric departments of one university and 11 teaching hospitals in the Netherlands.Population Women scheduled for labour induction with a singleton pregnancy in cephalic presentation at term, intact membranes and an unfavourable cervix; and without previous caesarean section.Methods Cost-effectiveness analysis from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 15 publications
2
40
3
Order By: Relevance
“…According to market values of both the prostaglandin analogues, the average cost of therapy of PGE2 group was significantly higher than that of the PGE1 group, so patients usually prefer PGE1 over PGE2. Similar results were observed by Van Barren et al 19 and Beckmann M et al 20 . In this study the cost of therapy was significantly less in the PGE1 group (Rs 9/-vs. Rs 406.57/-respectively) per woman.…”
Section: Figuresupporting
confidence: 90%
“…According to market values of both the prostaglandin analogues, the average cost of therapy of PGE2 group was significantly higher than that of the PGE1 group, so patients usually prefer PGE1 over PGE2. Similar results were observed by Van Barren et al 19 and Beckmann M et al 20 . In this study the cost of therapy was significantly less in the PGE1 group (Rs 9/-vs. Rs 406.57/-respectively) per woman.…”
Section: Figuresupporting
confidence: 90%
“…There was no morbidity for both mothers and neonates in both groups. When compared to previous studies foley induction seems more safe than prostin induction [5,8,10,11].We did not study the cost effectiveness of foley catheter compared to prostin but this was studied in previous studies and foley induction was found to be cheaper than prostin [1,3]. Women opinion was not studied but previous studies showed that more women were satisfied with foley induction especially that the pain was less than that of prostin induction [1,5,11].…”
Section: Discussionmentioning
confidence: 88%
“…Induction of labour is a common procedure in now a day's contemporary obstetrics [1][2][3]. Labour induction may be indicated by medical or obstetrical complications of pregnancy or may be requested or chosen for non-medical or social reasons [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in maternity there is the additional challenge of simultaneously considering the outcomes for both mother and child, and there is no accepted way to do this. Five economic evaluations of RCTs of IOL protocols have been published in the last 6 years [137,139,[218][219][220], but only one has reported QALYs.…”
Section: Discussionmentioning
confidence: 99%
“…Van Baaren [218], in a comparison of Foley catheters with PGE2 vaginal gel, reported that cost differences in the two groups predominantly originated from differences in the duration of labour ward stay. Eddama [219], in a placebo controlled RCT of outpatient isosorbide mononitrate prior to IOL, identified that the largest cost difference between groups was due to time spent in the antenatal ward.…”
Section: Discussionmentioning
confidence: 99%